Costs and benefits of the mixed-mating system of narcissus serotinus (amaryllidaceae) in the conservation of small fragmented populations - Draper, D. (2017)
Small fragmented populations often exhibit reduced plant-pollinator interactions and scarce outcrossing opportunities. In this context, mixed-mating systems can be advantageous since selfing can provide reproductive assurance, but they may also carry relevant costs such as those involved in inbreeding depression. This study examines the advantages and costs of selfing in Narcissus serotinus L., a mixed-mating geophyte that currently occurs in several fragmented populations in Portugal, that resulted from the construction of the largest European dam. Observation of pollinators revealed that cross-pollination is less frequent in small than in large populations. Manual self-pollinations significantly increased fruit and seed set in small-size populations, also suggesting limited insect pollination. The existence of selfing may provide reproductive assurance in small-size populations of N. serotinus where outcrossing pollination is reduced. Although floral biology and experimental pollinations showed that N. serotinus is capable of autonomous selfing, four of the six fitness traits studied showed significant inbreeding depression in all populations. The high levels of inbreeding depression found in N. serotinus suggest that the initial reproductive assurance advantage of selfing may be counterbalanced by lower survival of the resulting individuals and a decrease in the evolutionary potential of the populations.